Dual approach for high-efficiency graphene oxide reduction - Farasuraya, Che Zakaria; Siti Maznah, Kabeb; Nurul Huda, Abu Bakar (Elsevier, 2025)
This study presents a dual approach to synthesizing high-quality reduced graphene oxide (rGO) by integrating chemical and mechanical reduction methods. The aim is to enhance the reducing agent’s efficiency and refine structural properties. By combining chemical and mechanical reduction, this method optimizes graphene oxide (GO) properties through variations in NaOH concentration and ultrasonication time. Characterization was conducted using FTIR, XRD, XPS, FESEM, and ImageJ analysis to examine the structural and morphological attributes of the rGO. Results demonstrated that a 10 % NaOH concentration with 15 min of ultrasonication significantly enhances rGO structural quality by efficiently reducing oxygen-functional groups and increasing particle size. Notably, this condition exhibited a synergistic effect, achieving higher reduction efficiency than 5 % and 15 % NaOH at the same ultrasonication durations. This study also shows that an ultrasonication time between 15 min and 1 hour is sufficient and effective for GO reduction, however, GO sheets may begin to reassemble after 30 min of ultrasonication. This approach, combined with the utilization of NaOH, a widely available and low-toxicity reducing agent, suggests its potential for further optimization. Further research may explore alternative reducing agents and processing conditions to enhance rGO properties for broader protective coatings, larger-scale production, and industrial applications.